The lighting pattern book for homes - Leslie, Russell P (McGraw-Hill, 1996)
"The Lighting Pattern Book for Homes, written by the experts at the Lighting Research Center, contains accurate and up-to-date information on lighting products and techniques that will enable the architect, interior designer, electrical contractor or building professional to design energy-efficient lighting for the home. The lamps, luminaires and controls described are readily available and easy to install. The Lighting Pattern Book for Homes illustrates prototype designs or "patterns" for energy-efficient lighting that is suitable for typical dwellings. Common home lighting installations are shown along with several energy-efficient alternatives that upgrade or redesign the lighting."--Jacket.